Successful radioiodine treatment in a 3 year old child with Graves' disease following antithyroid medication induced neutropenia. Issue 2 (1st February 2003) - Rahman, M A S; Birrell, G; Stewart, H; Lucraft, H; Cheetham, T D
Abstract : A 3 year old child with Graves' disease and mitral valve prolapse became neutropenic on carbimazole therapy. She was switched to propylthiouracil but the neutropenia recurred. She was treated with radioiodine but required two doses of 113 MBq and then 198 MBq five months later before becoming hypothyroid. The mitral valve prolapse resolved when she was euthyroid on thyroxine replacement. Antithyroid drugs, surgery, and radioiodine all have a place in the management of the thyrotoxic child.